La Tribuna Illustrata, Domenica, 25 Luglio 1897 - Unknown (Massachusetts Institute of Technology. Libraries. Department of Distinctive Collections, 1897)
Issue of the Italian newspaper "La Tribuna Illustrato" with a front page color illustration of S.A. Andrée's balloon before its ascent from Svalbard. The accompanying article about Andrée's North Pole expedition is on page 235 and contains an illustration of Andrée. For more information about this item, visit https://archivesspace.mit.edu/repositories/2/digital_objects/810